Desalination of produced water via carbon dioxide hydrate using filter-based hydrate desalination reactor - Abulkhair, H. (2024)
This paper emphasizes sustainable development goal 6 and accepts that social progress and economic prosperity depend on the appropriate management of produced water. Produced water being the largest source of wastewater, several conventional desalination methods (thermal, membrane and freezeâthaw), are applied to obtain treated water. Nevertheless, the methods are highly energy intensive. Prospective utilization of hydrate-based desalination was proposed with a novel filter-based apparatus design to separate hydrate crystals from residual water and enhance the gasâliquid contact with all the unit operations (hydrate formation, and dissociation) occurring inside a single reactor. Experimentations were implemented to obtain the optimum conditions for CO2hydrate formation and compared with pure water. CO2 hydrate formation kinetics revealed induction time, moles consumed, water-to-hydrate conversion, and water recovery were 57 mins, 1.28 mol, 27.72 , and 50.65 at optimum conditions of 500 ml, 3.0 MPa, 450 rpm, and 275.15 K for purification of produced water. A desalination efficiency of 62â80 is achieved with each of the metal ions in the sequence K+>Na+>Mg2+>Ca2+, and anions SO42- > Cl- without any pre and post-treatment. Also, demonstrated that the ionic charge and size have a significant impact on the ion rejection mechanism. The findings disclosed that with an upsurge in the temperature to 277.15 K the desalination efficiency enhanced nevertheless the volume of formed hydrate is less resulting in less driving force. The total dissolved solids and electrical conductivity results indicate that the treated water meets Malaysia's water quality standards for irrigation purposes. This showcases the execution of the hydrate-based desalination process, investigating salt rejection and yield with our custom reactor design. The proposed reactor design may be utilized for the effective separation of hydrate and effectively desalinating waters of higher salinities. Hydrate-based desalination integrated with membrane reactors could lead to a sustainable source of clean water by treating produced water. Â© 2023 Elsevier B.V.